2018
DOI: 10.1186/s40490-018-0122-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of genetic diversity of Saraca asoca (Roxb.) De Wilde: a commercially important, but endangered, forest tree species in Western Ghats, India

Abstract: Background: Saraca asoca (Roxb.) De Wilde is a valuable tree used in traditional medicine against a variety of ailments. Almost all parts of the tree are used for various commercial herbal preparations. Due to overexploitation, the species is rapidly disappearing from Western Ghats where it is native and grew extensively until recently. Conservation of this important medicinal plant is therefore an urgent need. To plan effective conservation strategies, a scientific assessment of the genetic diversity and dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Higher level of genetic diversity was found amongst studied genotypes. In a current observe, RAPDS markers were applied for DNA fingerprinting and the population genetic shape of 7 wild and three cultivated populations totaling a hundred and sixty individuals of S. asoca in the Western Ghats location of Karnataka, Maharashtra and Goa for evaluation (Saini et al 2018). The examine showed that big stage of genetic variety existing in herbal populations of S. asoca, suggesting true natural pass-pollination, giving encouraging indicators that the gene pool is below no immediately chance.…”
Section: Biotechnological Approaches Towards Improvement Of Saraca Asmentioning
confidence: 92%
“…Higher level of genetic diversity was found amongst studied genotypes. In a current observe, RAPDS markers were applied for DNA fingerprinting and the population genetic shape of 7 wild and three cultivated populations totaling a hundred and sixty individuals of S. asoca in the Western Ghats location of Karnataka, Maharashtra and Goa for evaluation (Saini et al 2018). The examine showed that big stage of genetic variety existing in herbal populations of S. asoca, suggesting true natural pass-pollination, giving encouraging indicators that the gene pool is below no immediately chance.…”
Section: Biotechnological Approaches Towards Improvement Of Saraca Asmentioning
confidence: 92%
“…The banding pattern of the accessions were scored as, presence (1) or absence (0) and binary matrix was constructed [1], [5]. The number of polymorphic characters with each primer like Polymorphic Information Content (PIC) and Marker Index (MI) were recorded [1], [6]. Relationship between geographical and genetic distance and analysis of molecular variance (AMOVA) were carried out using GenAlEx 6.5 [7], [8].…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…All the SSR and AFLP markers revealed the existence of very narrow genetic base among the studied populations while RAPDs and ISSRs revealed high polymorphism, which could be attributable to the dominant nature of the markers. Recently, Saini et al (2018) studied genetic diversity in S. asoca trees in seven different forest areas and three cultivated sites located in central and north-central Western Ghats using RAPD markers. The within population variation was higher (89%) than among population diversity (11%), suggesting good natural crosspollination.…”
Section: Diversity Studiesmentioning
confidence: 99%